THE PERCEPTIONS OF TOURISM WORKERS IN NUSA DUA, BALI REGARDING THE USE OF ENGLISH LANGUAGE SKILLS IN THE TOURISM INDUSTRY - Suadnyana, I Wayan; Koeswiryono, Dika Pranadwipa (Universitas Hindu Negeri I Gusti Bagus Sugriwa Denpasar, 2024)
This paper examines the perceptions of tourism workers in Nusa Dua, Bali, regarding the importance of using English in the tourism industry. The study aims to explore the workers' perceptions and self-perceptions of English language skills and their relevance to the industry. A descriptive research design with a quantitative approach was utilized, and data were collected through questionnaires. The findings reveal that the participants hold positive self-perceptions and perceptions toward English language skills, strongly agreeing on the importance of English in their work. They recognize the significance of good listening, speaking, reading, and writing skills in English, as well as a broad vocabulary related to the industry. The study provides insights into the participants' background characteristics, including gender, age, education, departmental affiliation, and working experience. Overall, this research contributes to the understanding of the importance of English proficiency in the tourism industry, informing language training programs and human resource practices. The findings emphasize the participants' awareness of the role of English in effective communication, customer service, and career advancement, highlighting the need for language skills in the industry. Keywords: perceptions, English language skills, tourism industry